Industrial policy environment and private equity placement: Evidence from Chinese real estate firms - Yuping Ning; Rohaya Abdul Jalil (Economies, 2024)
Over the past four decades, China's real estate industry has experienced rapid growth, accompanied by frequent regulatory interventions. These shifts present an ideal context for examining the characteristics of private equity placements (PEPs) under varying industrial policy environments. This study examines the PEPs of Chinese real estate firms from 2006 to 2023, calculating the cumulative abnormal returns during announcement periods and the transaction discounts across various regulatory phases. The analysis reveals significant positive announcement effects, even in times of policy tightening, with these effects becoming more pronounced during periods of policy relaxation. However, regression analyses suggest that the policy environment does not significantly impact the announcement effects. Contrary to traditional views, PEP discounts tend to be shallower during policy tightening and deeper during policy loosening. Further analysis indicates that investors are willing to accept smaller discounts in exchange for more valuable investment opportunities.
Keywords: 330; PEP transaction; Chinese real estate companies; industrial policy environment; announcement effect; discount; certification effect